Rancang Bangun Sistem Informasi Keuangan Pribadi Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: Kwartir Ranting Tigaraksa) - Ahmad Fauzi Ridwan; Farizi Ilham; Rafly Tino Pratomo; Arya Wahyu Wibowo (CV. Shofanah Media Berkah, 2026)
Kwartir Ranting Tigaraksa is currently facing challenges in managing organizational finances, which are still handled manually, resulting in difficulties in recording transactions, risks of losing transaction evidence, duplicate entries, and delays in generating financial reports. This study aims to design and develop a web-based personal financial information system as a solution to enable more flexible and efficient fund management. The development method used is the Software Development Life Cycle (SDLC) with the Waterfall model, covering the stages of analysis, design, implementation using PHP and MySQL, and testing using the Black Box Testing method. Data collection was conducted through observation, literature review, and interviews with the chairman and executive board. The system includes nine main features, including transaction management, budgeting, real-time financial reporting, digital wallet management, recurring bills, report export, and Role-Based Access Control (RBAC) security. The system design is visualized using UML diagrams and the user interface is designed using Figma. This system is expected to assist administrators in monitoring financial conditions, managing recurring bills, and achieving budget targets in an organized manner, thereby improving organizational financial transparency and accountability.